"It's not their fault": Clinical facilitators' experiences supporting English as second language students - Lim, Eric; Kalembo, Fatch; Bosco, Anna; Ngune, Irene; Adebayo, Bola; Brown, Janie (Elsevier, 2022)
Background: International nursing students in Australia are faced with additional stress and challenges during clinical placements due to language and cultural differences. These factors can significantly impact their learning experience and personal wellbeing.